Economic optimum basis for regulation of nature management of systems of heat and power facilities in the preparation of technical water in electricity - Zhuravska, N. (Ways to Improve Construction Efficiency, 2020)
Obtaining thermal energy at heat facilities of heat supply systems by means of reagent-free water treatment is an innovative technology that has already confirmed its right to exist, solving many economic issues of production. The necessity of creation and application of subordinate two-level integrated indicator control over the technology of efficient water treatment in the heating systems of thermal power facilities of the construction industry has been confirmed. Subordinate control tools for water treatment technology must be used consistently, using: parameters of the state level results of water magnetization of the devices used, their equivalence to specific indicators in heating systems; specific indicators, indices (structural changes) and their consistency with certain potentials by purpose. The assessment of the whole system of conceptual and graphic model of reagent-free water treatment for its direction into the heat supply system of heat and power facilities of various industries, including the construction industry, housing and communal services, is carried out by the mechanism of passive monitoring. Scientific principles concerning development of indicator control system are offered. It is established that the quantitative characteristic of the constituent material flows of heating systems, as a measure of their additive functions and response to changes in catalytic activity, determines their subordinate indicator control mechanism. Two-level control involves: 1) the relationship between the apparatus for obtaining magnetized water (parameters) and the heating system (specific indicators and their indices); 2) the relationship between specific indicators that characterize the state of material flows of heating systems and trends in material flows under the conditions of electromagnetic fields. Studies of the trend of changes in the state of material flows were carried out according to a typological number of potentials (priority level): hydrochemical, electrophysical and thermophysical potentials. The indicator control system provides engineering and environmental aspects of reagent-free water treatment of systems of thermal power facilities of the construction industry.